Status and trends in world mushroom production-II -Mushroom production in Japan and China - Singh, Manjit; Kamal, Shwet; Sharma, Ved Parkash (Mushroom Research, 2018)
In last few decades, there have been changes in trends in amount and type of species under cultivation in different countries. New mushroom species are being cultivated and species that were not dominant in last century have gained prominence. For example in Japan at present six mushrooms viz., Flammulina velutipes, Hypsizygus ulmarius, Lentinula edodes, Grifola frondosa, Pleurotus eryngii and Pholiota nameko form the bulk of total mushroom production. In 80s, L. edodes was the most dominant mushroom but at present it is ranked third. Production of F. velutipes and H. ulmarius, which at present are number one and two, was very less in 80s. The production has increased in developing countries and is tending to stabilize or decline in developed countries. Despite these changes, the species other than button are still mainly cultivated in East even though these have made inroads into other countries. For example In China, a country that accounts for about 87% of world mushroom production, at present the dominant species under cultivation are Auricularia spp., Lentinula, Pleurotus spp., Flammulina velutipes and Agaricus bisporus. Contribution of Agaricus bisporus is only 15% of the total mushroom production. In the last decade there has been little change in the mushroom prices in Japan. There is shift towards fresh mushroom consumption. In East, except Japan, seasonal cultivation of mushrooms is mainly done whereas in West most of themushroom cultivation is under controlled conditions.